Оцінка процесів концентрації та консолідації банківського капіталу в країнах СНД та у світі - Бєлєнкова, О. Ю.; Цифра, Т. Ю.; Царюк, Т. М. (Ways to Improve Construction Efficiency, 2012)
The article analyzes the processes of concentration of the banking system in the world by the indices of concentration. Concentrations of bank capital all over the world according to ratio «tier one capital».